Regional Causes Of Iron Deficiency Anemia, Pathogenesis And Use Of Antianemic Drugs - Sulaymanova Gulnoza Tulkindzanovna; Amonov Muhammad Komilovich (The American Journal of Medical Sciences and Pharmaceutical Research, 2021)
The article describes the pathogenesis of occurring of iron deficiency anemia. The study was conducted in Bukhara. According to him, in each critical period, specific etiological factors predominate, and it is the elimination of these factors in the first place that increases the effectiveness of treatment. The main factors of iron defiency anemia are alimentary insufficiency of in girls of childbearing age is the onset of menstruation, and in women of childbearing age, improper use of intrauterine devices, frequent abortions, metroragias for various reasons, alimentary insufficiency and incomplete acceptance of the previous course of ferrotherapy.